2017
DOI: 10.1007/s11938-017-0144-0
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in the Elderly

Abstract: Dysphagia is a common problem in the elderly population with an especially high prevalence in hospitalized and institutionalized patients. If inadequately addressed, dysphagia leads to significant morbidity and contributes to decreased quality of life. Dysphagia can be categorized as emanating from either an oropharyngeal or esophageal process. A disproportionate number of elderly patients suffer from oropharyngeal dysphagia with a multifactorial etiology. Historically, treatment options have been limited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 64 publications
0
10
0
1
Order By: Relevance
“…Aging process has a clear influence on swallowing (19)(20)(21)(22)(23) . Swallowing capacity decreases as the individual gets older, with altered oral, pharyngeal and esophageal function (19) , manifested by prolongation of oral and pharyngeal phases (23) , esophageal motility abnormalities (23) , and reduction in the cross-sectional area of the upper esophageal sphincter opening during swallows (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Aging process has a clear influence on swallowing (19)(20)(21)(22)(23) . Swallowing capacity decreases as the individual gets older, with altered oral, pharyngeal and esophageal function (19) , manifested by prolongation of oral and pharyngeal phases (23) , esophageal motility abnormalities (23) , and reduction in the cross-sectional area of the upper esophageal sphincter opening during swallows (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Um planejamento de assistência multifacetada dentro das ILPI possibilita auxílio no retardo da progressão da sarcopenia e da obesidade sarcopênica. Já existem evidências que a adoção de exercícios físicos resistidos, uso de suplementos nutricionais e dietoterapia individualizada, protocolos de triagem para disfagia, atividades que estimulem a convivência social, devem fazer parte do plano de cuidados do idoso institucionalizado (OLIVEIRA et al, 2021;SMUKALLA et al, 2017;STRASSER et al, 2018).…”
Section: Discussionunclassified
“…Several studies have shown that rehabilitation and training can have significant positive effects in OD patients, and are recommended as supportive treatments (19,20,40). Swallowing intervention with exercise, such as rehabilitation and swallowing training, was also reported to improve swallowing dysfunction and ODrelated comorbidities (41,42).…”
Section: Rehabilitation and Trainingmentioning
confidence: 99%